A Holistic Review of the State‐of‐the‐Art Microfluidics for Exosome Separation: An Overview of the Current Status, Existing Obstacles, and Future Outlook. Issue 29 (28th May 2021) - Ding, Lihua; Yang, Xiaonan; Gao, Zibo; Effah, Clement Yaw; Zhang, Xiaoju; Wu, Yongjun; Qu, Lingbo
Abstract: Exosomes, a class of small extracellular vesicles (30–150 nm), are secreted by almost all types of cells into virtually all body fluids. These small vesicles are attracting increasing research attention owing to their potential for disease diagnosis and therapy. However, their inherent heterogeneity and the complexity of bio‐fluids pose significant challenges for their isolation. Even the "gold standard, " differential centrifugation, suffers from poor yields and is time‐consuming. In this context, recent developments in microfluidic technologies have provided an ideal system for exosome extraction and these devices exhibit some fascinating properties such as high speeds, good portability, and low sample volumes. In this review, the focus is on the state‐of‐the‐art microfluidic technologies for exosome isolation and highlight potential directions for future research and development by analyzing the challenges faced by the current strategies. Abstract : Microfluidic technology is one of the promising tools for exosome extraction because of its high efficiency, ability to save time and reagents, simplified operation, and high portability. To keep track of the state‐of‐the‐art advancements, a holistic review of microfluidic devices for exosome separation is provided. To highlight the direction for future development, the current challenges and outlook are also summarized.